From Development Aid to Development Partnerships – the End of Coloniality? Critical discourse analysis of DFID's development partnership with South Africa - Strand, Mia (African Studies, 2020)
Development aid discourses have been criticised for perpetuating othering and coloniality. The discourses have been argued to produce and reproduce conceptual creations of a distinguishable 'us' and 'them' through binaries of 'developed' and 'underdeveloped', and they have been stated to uphold lingering colonial and racial hierarchies where the former colonial powers remain preeminent and subjugate the 'Global South'. This decolonial critique of development aid discourses and their perpetuation of asymmetrical relationships between donor and recipient has led to the emergence of development partnerships. This discourse emphasises the levelling of the playing field, and mutual cooperation to achieve common development goals. The development partnership discourse thus appears to challenge the othering and coloniality inherent in former development aid discourses. In 2015, the United Kingdom's Department for International Development (DFID) ended their 'traditional' bilateral aid programme to South Africa and implemented a 'development partnership' in its place. DFID's development partnership discourse has previously been criticised for denying mutuality, however, and for perpetuating racialised hierarchies. The question is therefore whether the discourse surrounding DFID's development partnership with South Africa is perpetuating othering and coloniality, or whether it is establishing a relationship built on mutual interests and cooperation. This research paper analyses two DFID policy papers setting out the planning of the partnership approach, and four transcripts of interviews with representatives involved in the implementation of the development partnership. By applying Critical Discourse Analysis (CDA) the thesis analyses linguistic aspects of the discourse that serves to uphold certain power structures by defining decision-‐making. The CDA particularly focuses on the science, narrative and perceived 'truths' about development, the recontextualisation of its particular language and the interconnectedness with other discourses that continue to sustain and reproduce the discourse. The research finds a more nuanced approach to development, as conceptualised by the representatives involved in the implementation of the partnership, and that it is challenging the 'imperial gaze' inherent in development aid discourses. However, the analysis also reveals clear examples of othering and coloniality. This is evident through linguistic distancing through notions of time, relying on particular binaries, and referring to a naturalised development trajectory which denies lived experiences and subjugate South Africa as a country. The suggestion of mutuality therefore appears to be just a façade, and the development partnership discourse is rather emphasising difference and justifying colonial hierarchies.